Daily aciclovir for HIV-1 disease progression in people dually infected with HIV-1 and herpes simplex virus type 2: a randomised placebo-controlled trial - Lingappa, Jairam R; Baeten, Jared M; Wald, Anna; Hughes, James P; Thomas, Katherine K; Mujugira, Andrew; Mugo, Nelly; Bukusi, Elizabeth A; Cohen, Craig R; Katabira, Elly; Ronald, Allan; Kiarie, James; et al. (The Lancet (British edition), 2010)
Most people infected with HIV-1 are dually infected with herpes simplex virus type 2. Daily suppression of this herpes virus reduces plasma HIV-1 concentrations, but whether it delays HIV-1 disease progression is unknown. We investigated the effect of aciclovir on HIV-1 progression. In a trial with 14 sites in southern Africa and east Africa, 3381 heterosexual people who were dually infected with herpes simplex virus type 2 and HIV-1 were randomly assigned in a 1:1 ratio to aciclovir 400 mg orally twice daily or placebo, and were followed up for up to 24 months. Eligible participants had CD4 cell counts of 250 cells per μL or higher and were not taking antiretroviral therapy. We used block randomisation, and patients and investigators were masked to treatment allocation. Effect of aciclovir on HIV-1 disease progression was defined by a primary composite endpoint of first occurrence of CD4 cell counts of fewer than 200 cells per μL, antiretroviral therapy initiation, or non-trauma related death. As an exploratory analysis, we assessed the endpoint of CD4 falling to <350 cells per μL. Analysis was by intention to treat. The trial is registered with ClinicalTrials.gov, number NCT00194519. At enrolment, the median CD4 cell count was 462 cells per μL and median HIV-1 plasma RNA was 4·1 log 10 copies per μL. Aciclovir reduced risk of HIV-1 disease progression by 16%; 284 participants assigned aciclovir versus 324 assigned placebo reached the primary endpoint (hazard ratio [HR] 0·84, 95% CI 0·71–0·98, p=0·03). In those with CD4 counts ≥350 cells per μL, aciclovir delayed risk of CD4 cell counts falling to <350 cells per μL by 19% (0·81, 0·71–0·93, p=0·002) The role of suppression of herpes simplex virus type 2 in reduction of HIV-1 disease progression before initiation of antiretroviral therapy warrants consideration. Bill & Melinda Gates Foundation.